Book Reviews (Journal of Finance, 1999)
Abstract The Mutual Fund Business . By ROBERT C. POZEN. Cambridge, MA: MIT Press, 1998. Pp. xiii + 712. Risk Management and Insurance . By SCOTT E. HARRINGTON and GREGORY R. NIEHAUS. Irwin/McGraw‐Hill, 1999. Pp. xxx + 674.